Relationship of information-communication and interactive technologies in the process of training future teachers - Adobovska, Mariia Volodymyrivna (Journal of Education, Health and Sport, 2017)
The results of the analysis of the role of interactive methods of pedagogical interaction in the preparation of future teachers are presented. The relevance of the study is due to the need to design the content of educational programs for vocational training using interactive technologies in the context of the activity paradigm of education, aimed at improving its efficiency and quality. The author identified the pedagogical conditions for the implementation of interactive teaching methods. The interrelation of information-communication and interactive technologies, in particular the case-method, is presented in the process of training future teachers. The necessity of choosing interactive technologies of pedagogical interaction for the implementation of effective polylogic relationship of students with teachers and with each other is substantiated. In this connection, special training of teachers for the implementation of interactive methods in the system of training future teachers through refresher courses is required.